614.DEVELOPMENT OF INNOVATIVE BRAKE SYSTEM FOR ROLLING STOCK - Tasko, Smileski; Gligorce, Vrtanoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
In this paper is shown the importance of introducing innovative products in railway industry, especially when it comes to products from which depends the railway traffic safety, like the brake systems. These brake systems have the essential function of decelerating and stoping of rolling stock. Because the brake systems are a subject of large static and dynamic loads in external conditions, the development of this type of system is a long and complex process. In this paper is shown one part of innovative brake system development by using computer simulation.